Synthesis and Crystal Structure of trans-2-(2,4,6-Trimethylphenyl)-1-Nitroethylene - Zhao, Pei-Hua; Zhang, Mei; Zhao, Gui-Zhe (Asian Journal of Chemistry, 2013)
A nitroalkene compound, trans-2-(2,4,6-trimethylphenyl)-1-nitroethylene [C11H13NO2 (I)] has been synthesized and structurally characterized by elemental analysis, 1H (13C) NMR spectra and single-crystal X-ray diffraction. Compound (I) crystallizes in the triclinic, space group P-1 with a = 9.700(5), b = 13.784(7), c = 15.306(8) Å, a = 80.976(15), b = 84.85(2), g = 86.523(19)º, V = 2010.8(18) Å3, Z = 4, C22H26N2O4, Mr = 382.45, Dc = 1.263 g/cm3, F(000) = 816, μ (MoKa) = 0.087 mm-1, the final R1 = 0.0714 and wR2 = 0.1685 for 4737 observed reflections [I > 2s(I)]. In addition, X-ray analysis reveals that both the C-H···O short contacts and the p-p stacking interactions are observed in the crystal structure. The two kinds of intermolecular interactions extend the molecules into an infinite three-dimensional network.